Tracheostomy intervention in intubated COVID positive patients: A survey of current clinical practice among ENT surgeons. Issue 7 (5th June 2020) - D'Souza, Ayman; Simo, Ricard; D'Souza, Alwyn; Vaz, Francis; Prior, Andrew; Kanegaonkar, Rahul
Abstract: Introduction: The COVID‐19 pandemic has resulted in an unprecedented need for critical care intervention. Prolonged intubation and mechanical ventilation has resulted in the need for tracheostomy in some patients. The purpose of this international survey was to assess optimal timing, technique and outcome for this intervention. Methods: An online survey was generated. Otorhinolaryngologists from both the United Kingdom and Abroad were polled with regards to their experience of tracheostomy in COVID‐19 positive ventilated patients. Results: The survey was completed by 50 respondents from 16 nations. The number of ventilated patients totalled 3403, on average 9.7% required a tracheostomy. This was on average performed on day 14 following intubation. The majority of patients were successfully weaned (mean 7.4 days following tracheostomy). Conclusion: The results of this brief survey suggest that tracheostomy is of benefit in selected patients. There was insufficient data to suggest improved outcomes with either percutaneous vs an open surgical technique.